THE IMPACT OF INFLUENCERS ON TOURISM DIGITAL ADVERTISING IN THE REPUBLIC OF KARAKALPAKSTAN - Mirziyo Sodikov Odiljon ogli (American Journals, 2024)
In the rapid development of digital technology and the rise in the number of users, digital marketing is gaining momentum among businesses. In particular, businesses in the field of tourism are more interested in this type of marketing. The diversification of digital advertising tools is evolving continuously. Digital advertising investments are increasingly drawing the attention of marketing managers and becoming significant in the marketing policy of business. Directly or indirectly, the local population in the region influences advertising. As known, tourists heed the advice of fellow users on a tourist visit. Therefore, promoting their businesses via influencer feedback, blog entries, photo and video content influence tourists visiting the destination. The significance of this study is also due to the fact that there is currently no research on tourism digital advertising for this area. Therefore, the given study justifies the importance of digital advertising among businesses in the era of digital technology.The given study justifies the importance of digital advertising among businesses in the era of digital technology. Digital promotion includes various marketing tools. Influencers among them are currently in demand. It is established that influencer participation positively influences advertising views of both urban and regional areas of Uzbekistan. In addition, an assessment of the competencies of influencers operating in the tourism business, acceptance of their capabilities by the local population, and information about influencers operating in Karakalpakstan were given as a logical conclusion.